High-Tech Exposure Therapy for PTSD - Canavan, Neil (MD Conference Express, 2008)
Post-traumatic stress disorder (PTSD) first gained public awareness after the Vietnam War, as large numbers of returning veterans presented with depression and problems with substance abuse, which occur frequently with PTSD, and either a lack of or inappropriate emotional responses. As the Iraq War grinds into its fifth year, it’s not surprising that PTSD has regained the headlines.